Amphipods from tidal channels of the Gulf of Gabès (central Mediterranean Sea) - FERSI, ABIR; DAUVIN, JEAN CLAUDE; PEZY, JEAN PHILIPPE; NEIFAR, LASSAD (Mediterranean Marine Science, 2018)
The spatial and temporal species richness, abundance and assemblage structure of amphipods from four tidal channel of the Gulf of Gabès were studied at 26 stations and during four seasons from March 2016 to January 2017. This led to the identification of 4,278 individuals, 45 species and 21 families. The four mostly diversified families are the Ampeliscidae (6 species), the Caprellidae (5) and the Aoridae and Maeridae (4 species both), while three families account for 75% of the individuals: Aoridae (45.5 %), Corophiidae (20.5%) and Dexaminidae (7.2%). The species richness and abundance were higher in winter than at other seasons. The fauna is dominated by a small number of species characteristic of areas with detritus accumulation and seagrass meadows, including Microdeutopus anomalus, Monocorophium acherusicum, Dexamine spinosa, Microdeutopus gryllotalpa, Cymadusa filosa and Elasmopus rapax, which are commonly recorded in lagoons and coastal shallow waters of the Mediterranean Sea. The amphipod structure is linked to the location of tidal channels in the Gulf of Gabès. Abundances are low in the Kerkennah channel compared with other channels, especially the Maltine channel with high winter accumulation of organic matter. There are also low abundances in high-energy hydrodynamic zones with gravel sediment; conversely, the presence of macrophytes, mainly in the seagrass meadows, increases amphipod diversity. As a result of this study, five new species can be added to the inventory of the Tunisian marine amphipod fauna, including a non-native species for the Mediterranean Sea, Paracaprella pusilla.